2004
DOI: 10.1097/01.prs.0000111596.61137.a1
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Nerve Regeneration and Orientation across a Gap with a Nerve Graft within a Vein Conduit Graft: A Functional, Stereological, and Electrophysiological Study

Abstract: In this study, the right sciatic nerves of 40 rats were used to determine whether a nerve graft within a vein graft might accelerate and facilitate axonal regeneration, compared with a nerve graft alone. The animals were separated into four groups, as follows: group 1, sham control; group 2 (control), segmental nerve resection and no repair; group 3, segmental nerve resection and nerve grafting; group 4, segmental nerve resection and reconstruction with a nerve graft within a vein conduit graft. For all groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 26 publications
1
28
0
2
Order By: Relevance
“…In many of the previous animal studies, scar tissue was not found in vein conduit grafts. [10][11][12] Previous animal studies demonstrated regeneration of nerve fascicles through the vein conduit. 10,12,13 Electrophysiological studies also showed propagation of action potentials through the vein graft.…”
Section: Discussionmentioning
confidence: 99%
“…In many of the previous animal studies, scar tissue was not found in vein conduit grafts. [10][11][12] Previous animal studies demonstrated regeneration of nerve fascicles through the vein conduit. 10,12,13 Electrophysiological studies also showed propagation of action potentials through the vein graft.…”
Section: Discussionmentioning
confidence: 99%
“…Dans ces cas, la reconstruction au moyen de greffe ou procédure assimilée a de meilleurs résultats [3] et représente une option fiable et préférée par la plupart des chirurgiens [4,5].…”
unclassified
“…[17] Alternatively, Sahin et al created 1-cm defect on rat's tibial nerve and repaired it with minced nerve tissue in vein graft [23] and then placed 1 of the 3 equal-sized pieces of nerve graft into vein graft. Although they did not report details of their mincing process, subsequent outcomes were similar to those achieved with autogenous nerve grafts.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] Most successful vein graft repairs are observed in defects less than 3 cm in length. [14] Previous studies have demonstrated utility of filling inside of vein graft with nerve [17] or muscle…”
mentioning
confidence: 99%